Moderate deviations for stochastic tidal dynamics equations with multiplicative Gaussian noise. Issue 4 (4th March 2022) - Haseena, A.; Suvinthra, M.; Mohan, Manil T.; Balachandran, K.
Abstract : In this article, we consider the stochastic tidal dynamics equations perturbed by multiplicative Gaussian noise and discuss some asymptotic behaviors. A central limit theorem and a moderate deviation principle are derived for such systems. The results are proved using a variational method (based on weak convergence approach) developed by Budhiraja and Dupuis.